PROFITABILITY MODELLING AS A TARGET OF BANKING IN INDONESIA - Dewi Cahyani Pangestuti (Jurnal ASET (Akuntansi Riset), 2021)
The existence of banks is very important for a country because it plays a role in encouraging the economy of a country where banks provide lines of financing, savings, and lending so that, in the end, people's standard of living can increase. To be able to maintain banking survival, the company must be able to maintain its performance well, including by increasing high profitability, distributing dividends well, and maintaining the prospects of a growing business so that its performance is considered good. The research aims to analyze and find out the effect of capital adequacy, credit risk, and liquidity on the profitability of Conventional Commercial Banks listed on the Indonesia Stock Exchange (IDX). The sample in this study is a conventional commercial bank listed on the IDX for the period 2015-2019, as many as 41 companies. The data analysis technique used is a type of quantitative analysis. The results showed that capital adequacy and credit risk negatively affect profitability, but liquidity does not affect profitability. Furthermore, it is expected to be able to add variables that affect banking profitability and expand the research period and add research samples, not only for conventional commercial banks but also for Islamic banks.